THE LEGAL STATUS OF CHURCH PEWS IN CERTAIN CIVIL LAW JURISDICTIONS - Anatoliy A. Lytvynenko; Jevgenij G. Machovenko (International Comparative Jurisprudence, 2023)
Objects of common use in various houses of worship, one of which is a place in a church (church pew), suggest that parishioners have the right to use them, often for quite a long period of time. However, do parishioners have property rights to a place in a church? How can disputes about the inheritance of a place in a church be resolved? In what area of legal regulation does this issue lie? The historical judicial practice of different countries around the world is quite rich in such examples, with the oldest surviving in collections dating back to the 16th century. Moreover, courts have come to quite varied conclusions about the legal status of a place in a church, property rights to it (if any, and whether recognised by law or custom), issues of its inheritance, the right of the church leadership to seize a place in a church from the previous owner and transfer it to other parishioners, and other disputes. It should be noted that in the historical judicial practice of the Republic of Lithuania – namely in judgment of the Supreme Tribunal of the Republic of Lithuania No. 107 (1927) – the issue of the possession and inheritance of a place in a synagogue was also raised. The historical jurisprudence of various countries shows a very rich range of sources of law being applied in such disputes – from customary and proprietary to civil and ecclesiastical law. The authors primarily use the historical-legal method within this article, including the method of interpreting legal norms relating to legal status and proprietary or inheritance rights regarding church pews.